Intranasal Glioma with Post-Endoscopic Resection in 1 Year Old Infant: Case Report and Literature Review* - De Lucca, Maria Eduarda Turczyn; Antunes, Leonardo Cesar Ferreira; Maffini, Jhulia Farinha; de Alencar, Guilherme dos Santos; Munhos, Sue Hellen de Oliveira; de Morais, Rodrigo Leite; Barcelos, Carlos Eliseu; Torres, Rosângela Stadnick Lauth de Almeida (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Introduction Nasal gliomas - or nasal glial heterotopias - are rare congenital malformations, which correspond to 5% of the congenital nasal masses. It is a mass composed of mature glial tissue that can be located outside, inside or near the nasal region, and may or may not be connected to the brain by a fibrous pedicle. This report addresses a case of nasal glioma that suffered recurrence after endoscopic treatment.Case Report A 1-year-old boy has, since birth, a mass inside the left nostril, which obstructs and widens the bridge of the nose. Upon physical examination, it is observed that the mass does not increase in size with crying and presents negative transluminescence and Furstenberg test. Upon being biopsied, the lesion reveals malignancy and the presence of inflammatory cells. MRI ruled out communication with intracranial structures. The endoscopic resection of the heterotopia removed a mass of 3,0 × 2,5 × 1,7 cm, whose histological and immunohistochemical analysis revealed glial pattern cell proliferation in the nasal mucosa.Conclusion Considering that nasal glial heterotopy is frequently present at birth, and that newborns breathe predominantly through this route, early diagnosis of the lesion is of great importance, as it can cause signs and symptoms of respiratory distress. In addition, it is worth noting that the early approach also prevents bone deformities.
Keywords: nasal glioma; congenital malformations; endoscopic resection; respiratory stress; bone deformities